Pengaruh Pengetahuan Bisnis dan Perilaku Bisnis terhadap Kesejahteraan Nelayan di Sendang Sikucing Kendal - masriah masriah; Susanti Susanti (PPPM Polimarin, 2020)
Sendang Sikucing is one of the fishing villages located in Rowosari Subdistrict, Kendal Regency. Sendang Sikucing villagers rely only on fish catches, fish catches are not sold at the local Fish Auctioneer (TPI) because they have been tied to middlemen or inhabited the ijon system. This is very detrimental to both the fishermen themselves and reduce the Regional Native Income (PAD). The purpose of this research is to find out how far business knowledge and business behavior to the level of welfare of the fishing community in sendang sikucing village Rowosari District Kendal. Sendang Sikucing residents have a weak economic background and do not have their own capital, so each will go to sea they have to borrow capital to the middleman with the guarantee of fish produced must be sold to middlemen with the guarantee of fish. This research is quantitative research emphasizes the analysis on numerical data processed by statistical methods that examine the factors that occur and the results of the study will describe about